Is there evidence for flow variability as an organism-level stressor in fluvial fish?. Issue 1 (2nd January 2017) - Costa, M.J.; Lennox, R.J.; Katopodis, C.; Cooke, S.J.
ABSTRACT: Flow regime is a fundamental driver in fluvial ecosystems, shaping habitat structure and biodiversity, and sustaining ecological integrity. Fish respond to flow fluctuations but whether aspects of flow variability represent organism-level stressors is poorly understood. To find existing evidence of fluvial fish organism-level responses to flow variability (natural or anthropogenic), and whether it resulted in quantifiable stress (i.e. departure from homeostasis), we reviewed literature on the physiological responses of fish exposed to flow. Among 58 articles that we identified to be relevant to the research question, 40 reported whole-animal responses (tertiary responses to stress), 37 reported blood and tissue level changes (secondary responses to stress) and 18 reported neuroendocrine changes (primary responses to stress), exclusively or combined. Whole-animal responses (e.g. growth or disease resistance) were more commonly assessed due to their broader use in population and community dynamics studies. Due to their long-term character it was difficult to isolate flow variability as the only stressor and to understand the underlying mechanisms that culminated in a stress response. Our review indicates that flow variability can be a stressor for fish but it remains unclear if events such as floods or hydropeaking are inherently stressful per se. More experimentation is needed to find out if flow variability presents a stressor to fluvial fish, what thresholds trigger a stress response and to better understand the relative role of the different flow components. This knowledge can be used to define robust stress biomarkers (particularly for field studies) and propose adequate flow thresholds.